2012
DOI: 10.3892/ijo.2012.1608
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation and inhibition of the nuclear translocation of Oct4 during multistep gastric carcinogenesis

Abstract: Gastric cancer is the fourth most commonly diagnosed malignancy and the second leading cause of cancer-related mortality worldwide. Recent research suggests that tissue stem cells and the self renewal transcription factor, octamer-binding transcription factor 4 (Oct4), could be involved in the development of certain tumors. The aim of this study was to investigate the expression pattern of Oct4 in normal human stomach and during multistep gastric carcinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…It was revealed that the expression of OCT4 was elevated in the nucleus of cancer tissue cells and was associated with tumor differentiation; however, OCT4 did not correlate with tumor size and lymph node metastases. The present study, coupled with other studies, may indicate a possible association between OCT4 nuclear accumulation and turmorigenesis (23). OCT4 was also differentially expressed in pancreatic cancer cells with different degrees of differentiation, of which the Panc-1 cell line had the highest expression level of OCT4.…”
Section: Discussionsupporting
confidence: 84%
“…It was revealed that the expression of OCT4 was elevated in the nucleus of cancer tissue cells and was associated with tumor differentiation; however, OCT4 did not correlate with tumor size and lymph node metastases. The present study, coupled with other studies, may indicate a possible association between OCT4 nuclear accumulation and turmorigenesis (23). OCT4 was also differentially expressed in pancreatic cancer cells with different degrees of differentiation, of which the Panc-1 cell line had the highest expression level of OCT4.…”
Section: Discussionsupporting
confidence: 84%
“…These pluripotency-inducing factors have been detected in embryonic stem cells, as well as in normal cells and cancer cells, including gastric cancer (9). Although these factors are necessary in order for stem cells to acquire pluripotency, it has been suggested that they may have oncogenic potential in normal cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 There have been studies that reported that Oct4 is overexpressed in many kinds of cancers, such as, lung cancer, oral squamous cell carcinoma, GC, breast cancer, and esophageal cancer and ectopic expression may play a role in the improvement of disease. [20][21][22][23] Nevertheless, there is little relation between MUC5AC and Oct4 with clinical factors in GC, and contradictory findings have been reported. In addition to clinical outcome, lymph node and distant metastasis has been shown to be important factors for prognostic in GC.…”
Section: In Addition Low Expression Of Muc5ac and High Expression Ofmentioning
confidence: 99%